Sack and manufacturing method thereof
A sagger with a SnO2 protective layer addresses the issues of corrosion and thermal shock resistance in lithium ion cathode material firing, enhancing durability and recovery efficiency.
Patent Information
- Application Number
- JP2021554924
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2019-11-08
- Filing Date
- 2020-10-30
- Publication Date
- 2024-12-24
- Estimated Expiration
- 2040-10-30
AI Technical Summary
The durability of saggers used in firing lithium ion cathode materials is compromised due to the diffusion of lithium and cobalt, leading to reduced corrosion resistance and thermal shock resistance, and poor releasability, which affects the recovery efficiency and performance of the lithium ion cathode material.
A sagger with a protective layer containing at least 70% by mass of SnO2, optionally combined with ZrO2 and SiO2, is applied to the surface that contacts the lithium ion cathode material, enhancing corrosion resistance and thermal shock resistance while improving peelability.
The protective layer effectively suppresses the reaction between lithium and cobalt with the sagger components, ensuring excellent corrosion resistance and thermal shock resistance, thereby improving the recovery efficiency and reducing manufacturing costs.
Smart Images

Figure 0007605125000004 
Figure 0007605125000005 
Figure 0007605125000006
Abstract
Description
[Technical field]
[0001] The present invention relates to a sagger and a method for manufacturing the same. [Background technology]
[0002] Lithium ion secondary batteries are widely used as power sources for portable electronic devices such as mobile phones, notebook personal computers, etc. The positive electrode active material of lithium ion secondary batteries contains lithium-containing composite oxides (e.g., lithium cobalt composite oxide, lithium nickel composite oxide, lithium manganese composite oxide, lithium manganese cobalt composite oxide, lithium nickel cobalt composite oxide, etc.).
[0003] In general, the raw material of the positive electrode active material (hereinafter referred to as lithium ion positive electrode material) is sintered in a roller hearth kiln, which is a continuous furnace using a sagger. Conventionally, mullite and composite materials such as mullite-cordierite have been mainly used as the material for the sagger.
[0004] In addition, in order to improve corrosion resistance against alkaline vapor generated during firing of lithium ion positive electrode materials, saggers containing materials such as spinel and magnesia using basic materials have been developed (Patent Documents 1 and 2). [Prior art documents] [Patent documents]
[0005] [Patent Document 1] Japanese Patent No. 3352210 [Patent Document 2] Japanese Patent Publication No. 2003-165767 Summary of the Invention [Problem to be solved by the invention]
[0006] When the lithium ion positive electrode material is sintered, the lithium and cobalt contained in the lithium ion positive electrode material diffuse into the sagger and react with the components of the sagger body. The reactants deteriorate the durability of the sagger, shortening its lifespan and reducing the recovery efficiency of the lithium ion positive electrode material.
[0007] On the other hand, when the saggers have a high content of spinel or magnesia, as in Patent Documents 1 and 2, the corrosion resistance of the saggers is increased, but the thermal expansion coefficient is also increased. Usually, in the cooling process after firing during the production of a positive electrode active material, the saggers and the fired product are forcibly cooled in order to increase the production efficiency. Therefore, if the thermal expansion coefficient of the saggers is high, cracks are generated during the cooling process, reducing the thermal shock resistance, and leading to breakage or cracks during use.
[0008] In addition, the sagger is required to have good releasability from the lithium ion positive electrode active material obtained after firing the lithium ion positive electrode material. If the releasability is poor, the recovery efficiency of the lithium ion positive electrode active material from the sagger after firing decreases, and the reaction products of lithium and cobalt with the components of the sagger body are mixed into the lithium ion positive electrode active material, degrading its performance.
[0009] Therefore, an object of the present invention is to provide a sagger that has excellent corrosion resistance against the diffusion of lithium and cobalt during sintering of a lithium ion positive electrode material, and has excellent peelability from the sintered product and thermal shock resistance. [Means for solving the problem]
[0010] The inventors discovered that the above problem can be solved by providing a protective layer containing at least 70% by mass of SnO2 on the surface of the sagger body made of amorphous refractory material that comes into contact with the lithium ion positive electrode material, and thus completed the present invention.
[0011] That is, the present invention is as follows. 1. A sagger comprising a sagger body and a protective layer covering a surface of the sagger body, The protective layer contains at least 70 mass % SnO2. 2. A sagger for sintering a lithium ion positive electrode material, comprising a sagger body and a protective layer covering a surface of the sagger body that comes into contact with a lithium ion positive electrode material, The protective layer contains at least 70 mass % SnO2. 3. The sagger according to claim 1 or 2, wherein the protective layer comprises ZrO2. 4. The sagger according to any one of 1 to 3 above, wherein the protective layer contains SiO2. 5. The sagger according to any one of 1 to 4 above, wherein the combined content of ZrO2 and SiO2 is 2 to 50 mol % with respect to the combined content of SnO2, ZrO2 and SiO2 in the protective layer. 6. The sagger according to any one of 1 to 5 above, wherein the sagger body is made of a zircon-based monolithic refractory material. 7. The sagger according to any one of 1 to 6 above, wherein the porosity of the sagger body is 30 Vol % or less. 8. The bulk density of the sagger body is 1.8 g / cm 3 More than 5.0g / cm 3 8. The sagger according to any one of 1 to 7 above, which is as follows: 9. The thermal expansion coefficient of the sagger body is 0.1×10 -6 / ℃ or more 4.8×10 -6 9. The sagger according to any one of 1 to 8, wherein the temperature is 0.1 to 1.5° C. / ° C. or lower. 10. The thermal expansion coefficient of the protective layer is 3.5×10 -6 / ℃ or more 5.0×10 -6 10. The sagger according to any one of 1 to 9, wherein the temperature is 0.1 to 1.5° C. or lower. 11. A method for producing a sagger for firing a lithium ion positive electrode material, comprising: preparing a sagger body; and providing a protective layer on a surface of the sagger body that contacts a lithium ion positive electrode material, A method for manufacturing a sagger for sintering a lithium ion positive electrode material, wherein the protective layer contains at least 70 mass % or more of SnO2. Effect of the Invention
[0012] The sagger of the present invention, particularly the sagger for sintering lithium ion positive electrode material, is provided with a protective layer containing at least 70 mass% or more of SnO2 so as to cover the surface of the sagger body that comes into contact with the lithium ion positive electrode material. The protective layer suppresses the reaction between the lithium and cobalt contained in the lithium ion positive electrode material and the components of the sagger body, and the sagger has excellent corrosion resistance and thermal shock resistance. In addition, the protective layer of the sagger for sintering lithium ion positive electrode material of the present invention provides good peelability from the lithium ion positive electrode active material, which can improve the recovery efficiency of the lithium ion positive electrode material and reduce the production cost. [Brief description of the drawings]
[0013] [Figure 1] FIG. 1 is a cross-sectional view showing one embodiment of a sagger of the present invention. [Diagram 2] FIG. 2 is a diagram showing the surface of the sagger of Example 1 in which the lithium ion positive electrode material was fired once. [Diagram 3] FIG. 3 is a diagram showing the surface of a sagger of Example 3 in which the lithium ion positive electrode material was fired once. [Figure 4] FIG. 4 is a diagram showing the surface of a sagger of Example 4 in which the lithium ion positive electrode material was fired once. [Diagram 5] FIG. 5 is a diagram showing the surface of a sagger of Example 5 in which the lithium ion positive electrode material was fired once. [Figure 6] 6(a) and (b) are diagrams showing the surface of a substrate having the same composition as the protective layer of Example 10, in which the lithium ion positive electrode material was baked once. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0014] Hereinafter, an embodiment of the present invention will be described with reference to the drawings. Note that the present invention is not limited to the following description, and can be modified as appropriate without departing from the gist of the present invention.
[0015] <Sag pot for sintering lithium-ion positive electrode material> Fig. 1 is a side cross-sectional view of a sagger 1 for sintering a lithium-ion positive electrode material according to the present invention. As shown in Fig. 1, the sagger 1 for sintering a lithium-ion positive electrode material includes a sagger body 2 and a protective layer 3 that covers the surface of the sagger body 2 that comes into contact with the lithium-ion positive electrode material. In this embodiment, the protective layer 3 covers the entire inner surface 21 of the sagger body 2, which is composed of a bottom 211 and a wall surface 212 of the inner surface 21.
[0016] Refractories are materials that can withstand high temperatures, and are broadly divided into shaped refractories and unshaped refractories. Shaped refractories are a general term for refractories that are preformed and fired, while unshaped refractories are a general term for refractories in powder or clay form.
[0017] <<Bowl body>> The sagger body 2 is made of a monolithic refractory. The monolithic refractory used for the sagger body 2 is not particularly limited, but examples thereof include zirconia, zircon, mullite, cordierite, mullite-cordierite, chromia, magnesia-chrome with magnesia raw material and chromite as main aggregate, magnesia-spinel made of a solid solution of magnesia (MgO) and spinel (MgAl2O4), magnesia (MgO)-titania (TiO2)-alumina (Al2O3) or magnesia-spinel-alumina-titania refractories. In particular, it is preferable that the sagger body 2 is made of a zircon monolithic refractory, because ZrSiO4 and SnO2 contained in the protective layer 3 react at the interface between the sagger body 2 and the protective layer 3 to generate a silica layer, thereby improving the adhesion between the protective layer 3 and the sagger body 2.
[0018] The porosity of the sagger body 2 is preferably 30 Vol% or less, more preferably 26 Vol% or less, even more preferably 22 Vol% or less, and particularly preferably 20 Vol% or less. By making the sagger have a porosity of 30 Vol% or less, the physical strength of the sagger can be improved, and the adhesion with the protective layer can be increased, thereby extending the life of the sagger. The porosity of the sagger body 1 is preferably 3 Vol% or more, more preferably 8 Vol% or more, even more preferably 13 Vol% or more, and particularly preferably 15 Vol% or more. By making the sagger have a porosity of 3 Vol% or more, the thermal shock resistance can be improved and the sagger can be made lighter.
[0019] The bulk density of the sack body 2 is 1.8 g / cm 3 More than 5.0g / cm 3 It is preferable that the content is 2.0 g / cm or less, and more preferable that the content is 2.0 g / cm or less. 3 More than 4.8g / cm 3 More preferably, it is 2.2 g / cm or less. 3 More than 4.6g / cm 3 Generally, the smaller the bulk density, the smaller the heat capacity and the higher the thermal shock resistance. 3 By satisfying the above requirements, mechanical properties that can withstand use as a sagger body can be realized. The bulk density of the sagger body 1 is 4.9 g / cm 3 By satisfying the above condition, the heat capacity can be reduced, the electrical energy can be reduced, and the thermal shock resistance can be improved.
[0020] The thermal expansion coefficient of the sagger body 2 is 0.1×10 -6 / ℃ or more 4.8×10 -6 / °C or less, and more preferably 1.5×10 -6 / ℃ or more 4.6×10 -6 / °C or less, and more preferably 3.0 × 10 -6 / ℃ or more 4.4×10 -6 / °C or less, and particularly preferably 3.8 × 10 -6 / ℃ or more 4.3×10 -6 / ℃ or less, and 4.1×10 -6 / ℃ or more 4.25×10 -6 / °C or less. By setting the thermal expansion coefficient of the sagger body 1 within the above range, the thermal shock resistance can be improved and the stress generated in the protective layer due to the difference in the thermal expansion coefficient with the protective layer can be suppressed, thereby extending the life of the sagger. The thermal expansion coefficient is measured at room temperature to 1100°C in accordance with JIS R2207-2.
[0021] The shape and dimensions of the sack body 2 are not particularly limited, and any suitable shape can be selected as long as it can accommodate and sinter a lithium ion positive electrode material.
[0022] <<Protective layer>> The protective layer 3 contains at least 70 mass % or more of SnO2. The protective layer 3 suppresses the reaction between the lithium and cobalt contained in the lithium ion positive electrode material and the components of the sagger body, thereby improving corrosion resistance and thermal shock resistance. The protective layer 3 improves the peelability from the lithium ion positive electrode active material, thereby improving the recovery efficiency of the lithium ion positive electrode material.
[0023] The content of SnO2 in the protective layer 3 is preferably 80 mass% or more, more preferably 90 mass% or more, and particularly preferably 95 mass% or more, based on 100 mass% of the entire protective layer. When the protective layer 3 contains 70 mass% or more of SnO2, excellent corrosion resistance can be exhibited against the diffusion of lithium and cobalt contained in the lithium ion positive electrode material during firing of the lithium ion positive electrode material.
[0024] The protective layer 3 preferably contains ZrO2. By containing ZrO2 in the protective layer 3, the volatilization of SnO2 can be suppressed. The protective layer 3 preferably contains SiO2 in addition to ZrO2. By containing SiO2 in addition to ZrO2, an excellent effect of suppressing the volatilization of SnO2 can be exhibited from the early stage after the start of volatilization, and further, the adhesion between the sagger body and the protective layer can be improved.
[0025] The total content of SnO2, ZrO2 and SiO2 in the protective layer 3 is preferably 70 mass% or more, more preferably 85 mass% or more, even more preferably 95 mass% or more, and particularly preferably 98 mass% or more. The upper limit is not particularly limited, but is typically 99.5 mass% or less. By making the total content of SnO2, ZrO2 and SiO2 70 mass% or more, it is possible to exhibit excellent corrosion resistance of SnO2 against lithium and cobalt contained in the lithium ion positive electrode material.
[0026] With respect to the total content (100 mol%) of SnO2, ZrO2 and SiO2, the combined content of ZrO2 and SiO2 is preferably 2 to 50 mol%, more preferably 4 to 35 mol%, even more preferably 6 to 24 mol%, and particularly preferably 8 to 15 mol%.
[0027] The effect of suppressing the volatilization of SnO2 is sufficiently obtained by making the total content of ZrO2 and SiO2 2 mol% or more relative to the total content (100 mol%) of SnO2, ZrO2 and SiO2. The effect of improving the corrosion resistance of SnO2 is sufficiently obtained by making the total content of ZrO2 and SiO2 50 mol% or less.
[0028] In order to suppress the volatilization of SnO2 in high temperature environments from an early stage and to exhibit the excellent corrosion resistance of SnO2 against lithium and cobalt, it is preferable that the protective layer 3 contains 50 to 98 mol % SnO2, 1 to 35 mol % SiO2, and 1 to 35 mol % ZrO2, assuming the total content of SnO2, SiO2, and ZrO2 in the protective layer 3 to be 100 mol %.
[0029] In addition, by making the content of ZrO2 1 mol % or more relative to the total content of SnO2, ZrO2 and SiO2, the volatilization suppression effect of ZrO2 and ZrSiO4 can be sufficiently obtained.In addition, by making the content of SiO2 1 mol % or more, the volatilization suppression effect of ZrO2 and ZrSiO4 can be sufficiently obtained.
[0030] Furthermore, by setting the content of SiO2 to 35 mol % or less with respect to the total content of SnO2, ZrO2 and SiO2, the effect of improving the corrosion resistance by SnO2 can be sufficiently obtained.
[0031] Furthermore, by setting the content of ZrO2 to 35 mol % or less with respect to the total content of SnO2, ZrO2 and SiO2, the effect of improving the corrosion resistance by SnO2 can be sufficiently obtained.
[0032] Here, the protective layer 3 preferably contains ZrO2 in a range of 1 to 12 mol% based on the total content of SnO2, ZrO2 and SiO2. Also, the SiO2 content is preferably in a range of 1 to 12 mol% based on the total content of SnO2, ZrO2 and SiO2. Therefore, the SnO2 content is preferably in a range of 76 to 98 mol% based on the total content of SnO2, ZrO2 and SiO2.
[0033] By setting the content ratio of ZrO2 to the total content of SnO2, ZrO2 and SiO2 at 1 to 12 mol %, it becomes possible to dissolve substantially all of ZrO2 in the tin oxide crystal, and the effect of improving corrosion resistance by SnO2 can be sufficiently obtained.
[0034] By setting the content of SiO2 to 1-12 mol% of the total content of SnO2, ZrO2 and SiO2, the effect of suppressing volatilization by ZrO2 and ZrSiO4 and the effect of improving corrosion resistance by SnO2 can be sufficiently obtained. Furthermore, the adhesion between the sagger body and the protective layer can be improved.
[0035] The sintering process is generally performed at 1200 to 1600°C for 3 to 5 hours, and the amounts of SnO2, ZrO2 and SiO2 in the refractory composition can be adjusted according to the actual sintering conditions.
[0036] The other components are not particularly limited as long as they do not impair the properties of the refractory of the present invention, and include known components used in tin oxide refractories.
[0037] Other components include oxides such as Al2O3, SiO2, CaO, MgO, Li2O, CuO, Cu2O, ZnO, HfO2, Y2O3, ZnO, Mn2O3, CoO, TiO2, Ta2O5, CeO2, Sb2O3, Nb2O5, Bi2O3, UO2, and HfO2.
[0038] From the viewpoint of corrosion resistance against lithium and cobalt, it is preferable that the protective layer 3 does not contain Fe. The Fe content in the protective layer 3 is preferably 0.5 mass % or less, more preferably 0.3 mass % or less, and further preferably 0.05 mass % or less.
[0039] The thermal expansion coefficient of the protective layer 3 is 3.5×10 -6 / ℃ or more 5.0×10 -6 / °C or less, and more preferably 3.7×10 -6 / ℃ or more 4.7×10 -6 / °C or less, and more preferably 3.95 × 10 -6 / ℃ or more 4.5×10 -6 / °C or less, and particularly preferably 4.1 × 10 -6 / ℃ or more 4.3×10 -6 / ° C. By setting the thermal expansion coefficient of the protective layer 3 within the above range, it is possible to improve the thermal shock resistance and the adhesion to the sagger body.
[0040] <Manufacturing method of sintering sagger for lithium ion positive electrode material> The method of the present invention for producing a sagger for sintering a lithium ion positive electrode material includes a step of preparing a sagger body 2, and a step of providing a protective layer 3 on the surface of the sagger body 2 that comes into contact with the positive electrode material.
[0041] <<Preparing the sack body>> The sagger body 2 is prepared by adding an appropriate amount of binder material and water to the refractory raw material, kneading the mixture, molding (e.g., pressure molding using a friction press, etc.), drying (e.g., natural drying), and then firing. The firing temperature and time can be appropriately set.
[0042] <<Protective layer formation process>> The means for providing the protective layer 3 on the sagger body 2 is not particularly limited, and examples thereof include coating, sintering, and bonding.
[0043] (coating) The means for providing the protective layer 3 on the sagger body 2 by coating is not particularly limited, but examples thereof include coating, spray coating, and thermal spraying. Specifically, for example, a material containing at least 70 mass% or more of SnO2 is dispersed in a solvent such as pure water or ion-exchanged water to form a slurry, and then the inner surface of the sagger body 2, which is the surface that comes into contact with the positive electrode material, is spray-coated to form the protective layer 3. Then, the material is fired at 1200°C for 5 hours.
[0044] The thickness of the protective layer 3 formed by coating is preferably 1 mm or less, more preferably 800 μm or less, and more preferably 500 μm or less, in order to suppress cracks due to the difference in thermal expansion coefficient with the sagger body 2. In order to improve durability, the thickness is preferably 1 μm or more, more preferably 10 μm or more, even more preferably 50 μm or more, and particularly preferably 100 μm or more.
[0045] (Sintering) An example of a method for providing the protective layer 3 on the sagger body 2 by sintering is a method in which the material for the protective layer 3 is sintered simultaneously during sintering to produce the sagger body 2. Specifically, for example, after the material for the sagger body 2 is poured into a mold for the sagger body, a material for the protective layer 3 containing at least 70% by mass of SnO2 is poured before firing, and the sagger body 2 and the protective layer 3 are sintered simultaneously. By sintering the sagger body 2 and the protective layer 3 simultaneously, the sagger body 2 and the protective layer 3 can be more firmly fixed to each other, improving durability.
[0046] When the protective layer 3 is formed by coating or sintering, the material of the protective layer 3 preferably contains ZrSiO4 in addition to SnO2. By sintering a material containing ZrSiO4 in addition to SnO2, SiO2 is generated and ZrO2 is dissolved in SnO2. This allows the particles forming the protective layer to be bonded together with SiO2, and the adhesion between the sagger body and the protective layer becomes stronger. If ZrSiO4 is contained in excess of the solubility limit, ZrSiO4 remains as unreacted. This allows the particles forming the protective layer to be bonded together with SiO2 and ZrSiO4, and the adhesion between the sagger body and the protective layer becomes stronger. In addition, the presence of SiO2 and / or ZrSiO4 at the grain boundaries of SnO2 effectively suppresses the volatilization of SnO2.
[0047] The thickness of the protective layer 3 formed by sintering is preferably 10 mm or less, more preferably 5 mm or less, and particularly preferably 3 mm or less in terms of reducing costs and mass.
[0048] The SnO2 contained in the material of the protective layer 3 is preferably applied as particles, and the particle size of the particles is preferably adjusted appropriately by combining particles of different particle sizes, such as coarse particles, medium particles, fine particles, and fine particles, with a maximum particle size of, for example, 1 to 3 mm. In addition, in order to impart durability to the protective layer 3, in addition to the coarse particles, medium particles, fine particles, and fine particles, SnO2 having a particle size of, for example, 3 to 50 μm may be combined.
[0049] Here, for example, if the coarse particles are less than 1700μm and 840μm or more, the medium particles are less than 840μm and 250μm or more, the fine particles are less than 250μm and 75μm or more, and the fine particles are less than 75μm and 15μm or more, the materials containing these four types of particles are adjusted and mixed. Regarding these four types of aggregates alone, when these are taken as 100 mass%, the content ratios of the coarse particles are preferably in the range of 21-33 mass%, the medium particles are 15-28 mass%, the fine particles are 30-45 mass%, and the fine particles are 5-18 mass% in terms of filling the clay. Also, for example, SnO2 may be composed of particles of 50μm or less, and the thickness of the protective layer 3 can be set to 1mm or less.
[0050] In this specification, the particle size refers to a value measured in accordance with JIS R2552 (1977). SnO2 may be used after pulverizing used refractories, waste refractories, etc., and adjusting the particle size.
[0051] (Paste) The protective layer 3 is provided on the sagger body 2 by bonding, for example, by forming an adhesive layer on the surface of the sagger body 2 on which the protective layer 3 is to be formed, and then pressing the protective layer 3 onto the adhesive layer to integrate them. Examples of adhesives include glass, alumina-based adhesives, zirconia-based adhesives, and metals such as silicon. Specifically, for example, when the adhesive is glass, an adhesive layer containing glass particles is formed on the surface of the sagger body 2 on which the protective layer 3 is to be formed, and then the glass is baked and melted to integrate the protective layer 3 and the sagger body 2. The thickness of the adhesive layer is usually preferably 5 to 500 μm, and more preferably 10 to 200 μm.
[0052] When the protective layer 3 is formed by adhesion, the thickness of the protective layer 3 is preferably 10 mm or less, more preferably 5 mm or less. From the viewpoint of reducing costs and mass, the thickness is particularly preferably 3 mm or less, and even more preferably 1 mm or less.
[0053] The sagger for sintering lithium-ion positive electrode material manufactured as described above is covered on the surface of the sagger body 2 that comes into contact with the positive electrode material with a protective layer 3 containing at least 70 mass % or more of SnO2. The protective layer 3 suppresses the reaction between the lithium and cobalt contained in the lithium-ion positive electrode material and the components of the sagger body 2, resulting in a sagger for sintering lithium-ion positive electrode material with excellent corrosion resistance and thermal shock resistance. EXAMPLES
[0054] The present invention will be specifically described below with reference to examples and comparative examples, but the present invention should not be construed as being limited to these descriptions in any way.
[0055] (Preparation of the sagger body substrate: Examples 1-20, 25-27) The raw materials for the sagger body were mixed to obtain the composition shown in Table 1, filled into a sagger mold, and pressure molded using a friction press at a molding pressure of 44 MPa to form a plate-like sagger body with dimensions and external shapes of 150 mm x 150 mm x 10 mm (height) after firing. Next, after a natural drying process and an edge finishing process, the molded product was fired in a firing furnace to obtain a sagger body substrate. Examples 1 to 5 are comparative examples in which a protective layer was not formed on the sagger body substrate.
[0056] The porosity, density, and thermal expansion coefficient of the obtained sagger body substrate were measured. The porosity was measured in accordance with JISR2205 (1992). The thermal expansion coefficient was measured at room temperature to 1100°C in accordance with JISR2207-2 (2007). The bulk density and porosity were measured according to JISR2205 (1992).
[0057] (Formation of protective layer by spray coating: Examples 6 to 8, 12 to 20, 26 and 27) The protective layer material adjusted to have the composition shown in Table 1 was spray coated onto the sagger body substrate obtained as described above using a WA-200-251ZP manufactured by Anest Iwata Coating Solutions at a spray air pressure of 0.34 MPa to form a protective layer.
[0058] The SnO2 particles in the protective layers in Examples 6 to 8, 15 to 20, 26, and 27 had particle sizes and ratios of 45 mass% 0.05 mm, 20 mass% 0.01 mm, 13 mass% 0.003 mm, and 22 mass% 0.00087 mm. The SnO2 particles in the protective layers in Examples 12 to 14 had a particle size of 0.003 mm.
[0059] (Formation of protective layer by pasting: Examples 9 to 11 and 25) An adhesive layer containing 67% by mass of SiO2, 12% by mass of Al2O3, 7% by mass of B2O3, 5% by mass of MgO, 4.5% by mass of CaO, and 4.5% by mass of SrO was formed on the sagger body substrate obtained as described above, and the adhesive layer was baked at 1150°C. After that, a protective layer having the composition shown in Table 1 was pressed against the adhesive layer at a pressure of 0.3 MPa for 1 minute to be integrated.
[0060] (Formation of protective layer by sintering: Examples 21 to 24) The raw materials for the sagger body were mixed to have the composition shown in Table 1, and filled into a sagger mold, after which the raw materials for the protective layer, with the composition shown in Table 1, were filled inside the sagger body. Using a friction press, the mixture was pressurized at a molding pressure of 44 MPa to form a plate-like sagger body with dimensions and external shape of 150 mm x 150 mm x 10 mm (height) after firing. Next, after a natural drying process and an edge finishing process, the molded product was fired in a firing furnace to form a protective layer on the sagger body substrate.
[0061] The SnO2 particles in the protective layers of Examples 21 to 24 had particle sizes and ratios of 27% by mass of 1.7 mm, 22% by mass of 0.68 mm, 35% by mass of 0.24 mm, and 16% by mass of 0.003 mm.
[0062] The thickness of the protective layer formed as described above was measured. The porosity, bulk density, and thermal expansion coefficient were measured by preparing a sample with a protective layer thickness of 5 mm and cutting out and processing the protective layer to use the measurement sample. The porosity was measured in accordance with JISR2205 (1992). The thermal expansion coefficient was measured at room temperature to 1100°C in accordance with JISR2207-2 (2007).
[0063] <Firing of lithium-ion cathode materials> 15 g of lithium ion positive electrode material (10 g of lithium carbonate, 5 g of cobalt oxide) was tapped onto the substrate prepared as above so as to have an area of 50 mm in diameter. The temperature was raised to 1050°C over 4 hours, held at that temperature for 10 hours, and then cooled to room temperature over 6 hours.
[0064] (Measurement of adhesion amount) The amount of adhesion was measured by turning the substrate over after baking the lithium ion positive electrode material, leaving it still for 5 seconds, and then measuring the amount of adhesion of the lithium ion positive electrode material.
[0065] (Measurement of maximum number of uses) Using a 150 x 150 x 10 mm plate, a repeated reaction test was carried out on the firing of the lithium ion positive electrode material. The adhered lithium ion positive electrode material was peeled off with a spatula. The temperature was raised to 1050°C over 4 hours, held for 10 hours, and then cooled from 1050°C in the air in one go. The maximum number of uses was determined to be the point at which cracks appeared in the sagger body substrate or the protective layer peeled off and the lithium ion positive electrode material was mixed into the sagger body substrate, and testing was stopped when it reached 50 uses.
[0066] The results are shown in Tables 1 to 3. For Examples 1, 3, 4 and 5, the surfaces of the saggers after sintering the lithium ion positive electrode materials are shown in Figures 2 to 5, respectively. Also, Figures 6(a) and (b) show the results of sintering the lithium ion positive electrode materials on a substrate (thickness 20 mm) having a protective layer with the same composition as in Example 10. Examples 1 to 5, 7 and 8 are comparative examples. Examples 9 and 13 are reference examples. Example 6, 10~12 and 14~27 is an example embodiment.
[0067] [Table 1]
[0068] [Table 2]
[0069] [Table 3]
[0070] As shown in Tables 1 to 3, the examples had better peelability from the positive electrode active material and better corrosion resistance and thermal shock resistance than the comparative examples, due to the provision of a protective layer containing at least 70 mass% SnO2 covering the surface of the sagger body that comes into contact with the positive electrode material. In addition, the results of Examples 6 and 12, in which the protective layer was formed by coating, revealed that when the protective layer is formed by coating, the thickness of the protective layer is preferably 1 mm or less in order to suppress cracks due to the difference in thermal expansion coefficient with the sagger body.
[0071] As shown in Figs. 6(a) and (b), when a lithium ion positive electrode material was sintered on a substrate containing at least 70% by mass of SnO2, the lithium ion positive electrode material was not attached to the contact surface of the substrate with the lithium ion positive electrode material, and when tilted, it slid down under its own weight, and the formation of a reaction layer was hardly observed. In contrast, Figs. 2 to 5 show the results of sintering a lithium ion positive electrode material on a substrate not forming a protective layer containing at least 70% by mass of SnO2. In Fig. 2, the entire contact surface of the substrate with the lithium ion positive electrode material turned brown, and a brown product layer protruding from the substrate was observed. In Figs. 3 to 5, an LCO layer was formed on the contact surface after the lithium ion positive electrode material was sintered, and was firmly attached to the substrate.
[0072] Although the present invention has been described in detail with reference to specific embodiments, it is apparent to those skilled in the art that various changes and modifications can be made without departing from the spirit and scope of the present invention. This application is based on a Japanese patent application (Patent Application No. 2019-203486) filed on November 8, 2019, and is incorporated by reference in its entirety. In addition, all references cited herein are incorporated in their entirety. [Explanation of symbols]
[0073] 1 Sack for firing lithium-ion cathode material 2. Sack Bowl Body 211 Bottom 212 Wall 21 Inner surface 3 protective layer
Claims
1. A sagger comprising a sagger body and a protective layer covering a surface of the sagger body, The protective layer contains at least 70% by mass of SnO 2 and ZrO 2 and SiO 2 ; The protective layer has a total content of ZrO 2 and SiO 2 of 2 to 50 mol % based on the total content of SnO 2 , ZrO 2 and SiO 2 .
2. A sagger for sintering a lithium ion positive electrode material, comprising: a sagger body; and a protective layer covering a surface of the sagger body that comes into contact with the lithium ion positive electrode material, wherein the protective layer is made of at least 70 mass % SnO 2 and ZrO 2 and SiO 2 ; The protective layer has a total content of ZrO 2 and SiO 2 of 2 to 50 mol % based on the total content of SnO 2 , ZrO 2 and SiO 2 .
3. 3. The sagger according to claim 1, wherein said sagger body is made of a zircon-based monolithic refractory material.
4. The sagger according to any one of claims 1 to 3, wherein the porosity of the sagger body is 30 Vol % or less.
5. The bulk density of the sagger body is 1.8 g / cm 3 5.0g / cm or more 3 A sagger according to any one of claims 1 to 4, wherein:
6. The thermal expansion coefficient of the sagger body is 0.1×10 -6 / ℃ or more 4.8 x 10 -6 The sagger according to any one of claims 1 to 5, wherein the temperature is 0.15 to 1.5°C or lower.
7. The thermal expansion coefficient of the protective layer is 3.5×10 -6 / ℃ or more 5.0 x 10 -6 The sagger according to any one of claims 1 to 6, wherein the temperature is 0.15 to 1.5°C or less.
8. A method for producing a sagger for sintering a lithium ion positive electrode material, comprising: preparing a sagger body; and providing a protective layer on a surface of the sagger body that contacts a lithium ion positive electrode material, The protective layer is at least 70% by mass of SnO 2 and ZrO 2 and SiO 2 ; The method for producing a sagger for sintering a lithium ion positive electrode material, wherein the protective layer contains 2 to 50 mol % of ZrO 2 and SiO 2 in total based on the total contents of SnO 2 , ZrO 2 and SiO 2 .
Citation Information
Patent Citations
Spinel refractory and use of the same
JP2003165767A
Corrosion-resistant burning tool and method of manufacturing the same
JP2010281471A
Heat treatment vessel
JP2014228239A
Lithium ion battery electrode material firing pot and protective layer of the same
JP2019121601A
Head-mounted image display device
JP3352210B2
